Risk factors for actinic keratosis, non‐melanoma skin cancer and cutaneous malignant melanoma in persons with and without Parkinson's disease: A cross‐sectional study - Esther Azizi; Hana Feuerman; Idit Peleg; Felix Pavlotsky; Zvi Segal; Bernice Oberman; Nirit Lev; Emmilia Hodak; Ruth Djaldetti; Sharon Hassin‐Baer; Rivka Inzelberg (Skin Health and Disease)
Abstract Background An epidemiological link between Parkinson's disease (PD) and cutaneous malignant melanoma (CMM) has been widely reported. The role of CMM risk factors in this association is unclear. Objectives To compare rates of risk factors for skin tumours, specifically actinic keratosis (AK), non‐melanoma skin cancer (NMSC) and CMM, between persons with and without PD. Methods In this cross‐sectional observational study, patients attending tertiary PD clinics and community controls were interviewed for background/medical data and underwent dermatological examination. Logistic regression models assessed risk factors for skin tumours and their interactions with PD status. Results Included were 141 persons with PD and 155 controls; mean age 71.7 and 72.6 years, respectively. In both groups, the majority were males of Ashkenazi origin. Altogether, AK, basal cell carcinoma, squamous cell carcinoma and CMM were recorded in 76 (53.9%) persons with PD and 92 (59.3%) controls (NS). CMM prevalence predominated in PD patients. In the PD group, prolonged sun exposure (p = 0.007), freckles (p < 0.001) and solar lentigines (p = 0.008) were associated with skin tumours. In the control group, dysplastic atypical moles were negatively associated with skin tumours (p = 0.017). Logistic regression of the whole cohort showed that older age (p < 0.001), fair complexion (p = 0.04) and prolonged sun exposure (p = 0.01) were associated with skin tumours, but PD status was not independently associated, and no interactions were found between PD status and CMM risk factors. Conclusions Periodic dermatological screening of PD populations is mandatory, especially for carriers of major phenotypic risk factors or presenting with AK, NMSC or CMM.